Building back better in small Island developing states in the pacific: Initial insights from the bind model of disaster risk management policy options in Fiji - Nepomuk Dunz; Hajime Tanaka; Nagisa Shiiba; Junko Mochizuki; Syed Ali Asjad Naqvi (Asian Development Bank Institute (ADBI), 2021)
Building resilience to disasters continues to pose challenges for developing countries. Historically, small island developing states (SIDS) bordering the Pacific Ocean have suffered from multiple hazards, such as earthquakes, coastal erosion, floods, and cyclones. Population increase, uneven progress in socioeconomic development, and the ongoing environmental degradation, including climate change, have exaggerated their vulnerability to disasters. At the same time, the recent COVID-19 global pandemic has shown that the small, remote, and less-diversified economies of SIDS are particularly prone to additional external shocks. Events such as COVID-19, in combination with disasters resulting from natural hazards, pose additional challenges for resource-constrained economies' recovery. However, the existing literature has rarely evaluated such interactions. This study hence provides initial insights into the interaction of alternative DRM policies in the presence of additional demandside constraints, which we evaluated through the recently developed binary constrained disaster (BinD) model. Our results indicate that a targeted increase of government spending in times of crisis could be beneficial for the economic recovery of Fiji. However, short-term trade-offs emerged with respect to financing options. Debt-financed recovery allows a faster and less painful recovery but requires quick and preferential access to foreign borrowing. Tax-financed recovery can compensate for short-term foreign borrowing needs but comes at the cost of more detrimental impacts on the GDP and private sector consumption.
Keywords: C22; Q54; H84; 330; blue economy; disaster risk reduction; build back better; BinD Model